PENGGUNAAN MASKER (PERSONAL PROTECTIVE EQUIPMENT ) DALAM UPAYA HIRARCHI OF CONTROLLING UNTUK MENCEGAH COVID-19 DITINJAU DARI ASPEK KESELAMATAN PADA MASYARAKAT RW 3 KEL. SUMAHILANG - Makomulamin Makomulamin; Nila Puspita Sari; Eka Sudaryati; Sarifah Rohil Pahlapi (Institut Kesehatan dan Teknologi Al Insyirah, 2023)
The World Health Organization (WHO) released data on cases that occurred in all countries, the trend shows a very significant increase, so this is a serious concern. In Indonesia, the number of cases continues to increase and it takes many lives. According to the National Institute of Occupational Safety and Health (NIOSH) Hierarchy Of Controls (HOC) is a system used to minimize or eliminate exposure to hazards. The hazard has the potential to cause loss / loss. One of the effective efforts to break the chain of the spread of Covid-19 is the application of the HOC, namely the use of masks. The use of masks is part of PPE / Personal Protective Equipment. PPE in the control hierarchy is included in the last effort made in reducing exposure to potential sources of danger of contracting Covid 19. The use of masks is a very effective preventive measure in preventing saliva droplets from Covid 19 sufferers from spreading the virus to other healthy people. This research is to determine the effectiveness of using masks in an effort to reduce the rate of spread of Covid-19 in RW 3, Sumagulung Village. This type of research is observational with a qualitative analytic approach by conducting in-depth interviews. Data processing techniques used triangulation, data analysis using content analysis to obtain in-depth information from informants. The results of the study show that the use of masks in the community at RW 3 Sumagulung Village has not been effective in preventing the transmission of Covid-19, the community does not really pay attention to the type of mask used, the community does not care about how to use masks that have been recommended by the government. It is hoped that the Kelurahan together with the Puskesmas will always provide understanding to the community through health promotion in increasing knowledge and safe behavior against the dangers of Covid-19.